1998
DOI: 10.1038/33929
|View full text |Cite
|
Sign up to set email alerts
|

Lipids are required for directional pollen-tube growth

Abstract: Successful pollination and fertilization are absolute requirements for sexual reproduction in higher plants. Pollen hydration, germination and penetration of the stigma by pollen tubes are influenced by the exudate on wet stigmas and by the pollen coat in species with dry stigmas. The exudate allows pollen tubes to grow directly into the stigma, whereas the pollen coat establishes the contact with the stigma. Pollen tubes then grow into the papillae, which are covered by a cuticle. The components of the exudat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
265
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 332 publications
(274 citation statements)
references
References 28 publications
9
265
0
Order By: Relevance
“…Evidence for water as a polarity signal has come from in vitro experiments with Nicotiana pollen: immersing these grains in purified lipids or in stigma exudates, and providing a nearby aqueous interface, results in polarized growth toward the aqueous medium, mimicking behavior in vivo. The pollen tubes emerge from the aperture closest to the hydrophobic-aqueous interface, suggesting that the source of water provides directional cues that establish polarity Wolters-Arts et al, 1998). Not only does this example implicate water, it also suggests a role for lipids in establishing polarity.…”
Section: Pollen Polarization and Germination: Preparing For Pollen Tumentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence for water as a polarity signal has come from in vitro experiments with Nicotiana pollen: immersing these grains in purified lipids or in stigma exudates, and providing a nearby aqueous interface, results in polarized growth toward the aqueous medium, mimicking behavior in vivo. The pollen tubes emerge from the aperture closest to the hydrophobic-aqueous interface, suggesting that the source of water provides directional cues that establish polarity Wolters-Arts et al, 1998). Not only does this example implicate water, it also suggests a role for lipids in establishing polarity.…”
Section: Pollen Polarization and Germination: Preparing For Pollen Tumentioning
confidence: 99%
“…Mutations that eliminate this secreted matrix cause female sterility; this defect can be bypassed by adding exogenous lipids (Goldman et al, 1994;Wolters-Arts et al, 1998). The addition of cis-unsaturated triacylglycerides is sufficient for hydration and germination, even on stigmaless tobacco plants .…”
Section: Pollen Hydration: Activating Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…A single homolog of chemocyanin may also be involved in pollen tube guidance in Arabidopsis (Arabidopsis thaliana), according to in vivo experiments (Dong et al, 2005). A gradient of the concentration of water in lipids (triacylglycerides) on the stigmas of tobacco (Nicotiana tabacum) and Arabidopsis was proposed to be critical for the initial directional growth of the pollen tube entering the stigma (Wolters-Arts et al, 1998). Transmitting tissuespecific protein in tobacco Wu et al, 1995Wu et al, , 2000 and stigma/stylar Cys-rich adhesin and pectin in lily (Mollet et al, 2000;Park and Lord, 2003) were identified in style tissue and shown to be necessary for the growth of the pollen tube in the style.…”
mentioning
confidence: 99%
“…Lipid metabolism and signaling potentially play important roles in several stages of fertilization, starting with production and release of viable pollen (Sanders et al, 2000;Stintzi and Browse, 2000) and synthesis of the protein-and lipidrich pollen coat, which has a protective function and provides essential signals for binding, recognition, and hydration by the stigma (Zinkl et al, 1999). Deficiencies in pollen coat lipids lead to hydration defects and conditional male sterility in Arabidopsis cer mutants (Preuss et al, 1993;Fiebig et al, 2000) and pollen coat lipids have also been suggested to direct a water gradient, which is required for organization of cell polarity prior to germination (Wolters-Arts et al, 1998).…”
mentioning
confidence: 99%